Work engagement and burnout among Polish labour migrants - Michał Kulisz; Antoni Wontorczyk (International Journal of Occupational Medicine and Environmental Health)
Objectives The aim of the study was to examine the relationship between work engagement, burnout and coworker support, social climate at work, work-language proficiency and post-migration job skill change, among international migrant workers.